PENGEMBANGAN ANGKUTAN PEMADU MODADI BANDARA NGURAH RAI - Agustini, Eka Tamar; Suthanaya, Putu Alit; Priyantha Wedagama, Dewa Made (JURNAL SPEKTRAN, 2018)
NgurahRai Airport is the third busiest international airport in Indonesia, after Soekarno-Hatta and Juanda International Airport. NgurahRai Airport services need to be improved, one of them with the development of integrated mode transport route at NgurahRai Airport. The purposes of this research are to analyze the potential demand and characteristic operational systemof integrated mode transport.Based on the results of analyses, it was found that potential demand of integrated mode transport is 15.385 people in 2016 and it is estimated to be 16.154 people in 2017. The number represents the amount of demand of the integrated transport mode for the eight routes of service. The service time is designed for 16 hours / day, divided into two shifts. The first shift operates from 05.00 A.M  untill  13:00 PM, followed by  the second shift that begin at 13.00 PM to  21:00 PM. The fare is IDR. 10.000 for all routes except Route 8 is IDR 4.500. Keywords : integrated mode transport, potential demand , operational system.